2019
DOI: 10.1080/21645515.2019.1697595
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and safety of a multi-dose quadrivalent inactivated influenza vaccine in individuals aged 6 months to 17 years: a randomized phase III trial

Abstract: (2020) Immunogenicity and safety of a multidose quadrivalent inactivated influenza vaccine in individuals aged 6 months to 17 years: a randomized phase III trial,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
3
0
2
Order By: Relevance
“…However, poor vaccination responses were not associated with high pre-vaccination antibody titers in the present study. Recent clinical trials demonstrate that inactivated influenza vaccines are immunogenic and effective in previously-naïve infants [ 64 , 65 , 66 , 67 ], indicating that these vaccines can prime naïve B cells. However, memory B cells are intrinsically programed to out-compete naïve B cells upon B cell receptor engagement [ 68 , 69 , 70 ], and it has been proposed that this could account for the observation that antibody responses to A(H1N1pdm09) vaccines were highly focused on epitopes shared with previously encountered A(H1N1) viruses in selected age groups [ 41 , 71 , 72 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, poor vaccination responses were not associated with high pre-vaccination antibody titers in the present study. Recent clinical trials demonstrate that inactivated influenza vaccines are immunogenic and effective in previously-naïve infants [ 64 , 65 , 66 , 67 ], indicating that these vaccines can prime naïve B cells. However, memory B cells are intrinsically programed to out-compete naïve B cells upon B cell receptor engagement [ 68 , 69 , 70 ], and it has been proposed that this could account for the observation that antibody responses to A(H1N1pdm09) vaccines were highly focused on epitopes shared with previously encountered A(H1N1) viruses in selected age groups [ 41 , 71 , 72 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lo studio di fase III di Ojeda et al [ 35 ] randomizzato, in aperto, è stato condotto per valutare l’immunogenicità e la sicurezza di un vaccino QIVe in formato multi dose ( multi-dose vial , MDV), contenente tiomersale rispetto al formato a dose singola ( pre-filled syringe , PFS) senza tiomersale. Lo studio ha arruolato 302 soggetti (121 soggetti di età compresa tra 6 e 35 mesi, 59 di età compresa tra 3 e 8 anni e 122 di età compresa tra 9 e 17 anni) tra il 19 dicembre 2017 e il 19 gennaio 2018.…”
Section: Immunogenicità Efficacia Teorica E Sul Campounclassified
“…Nello studio di Ojeda et al [ 35 ] sono stati riportati i dati di sicurezza di un vaccino QIVe in formato multi dose (QIV-MDV), contenente tiomersale rispetto alla preparazione in dose singola (QIV-PFS) senza tiomersale, in bambini di età compresa tra i 6 mesi e i 18 anni. Nei soggetti di età 6-35 mesi nessun AE immediato non sollecitato è stato segnalato sia nei riceventi QIV-MDV che nei vaccinati con QIV-PFS, le reazioni sollecitate globali sono risultate pari al 72% nei vaccinati con QIV-MDV e al 59,3% negli immunizzati con QIV-PFS, le reazione sollecitate al sito d’iniezione erano pari al 54% nei QIV-MDV e al 48,1% nei QIV-PFS, mentre le reazioni sollecitate sistemiche sono risultate pari al 66% nei QIV-MDV e al 46,3% nei QIV-PFS, mentre le reazioni non sollecitate non gravi globali sono risultate pari al 52,5% nei QIV-MDV e al 43,1% nei QIV-PFS.…”
Section: Sicurezza E Tollerabilitàunclassified
“…Four of the included studies evaluated quadrivalent influenza vaccines (QIV) in children. 5,[11][12][13] All of the studies reported reactogenicity outcomes and adverse events. One study reported both TIV and QIV vaccines and the results are reported above.…”
Section: Quadrivalent Influenza Vaccinesmentioning
confidence: 99%
“…11 The final trial evaluated Vaxigrip Tetra (15μg/strain) administered to children and adolescents in two different formats. 12 Vaxigrip administered as a single dose using a pre-filled syringe (PFS) was compared to a 10-dose multi-dose vial (MDV). Systemic reactions were reported in more infants aged 6 − 35 months in the MDV group than in the PFS group, however this difference was not clinically significant.…”
Section: Quadrivalent Influenza Vaccinesmentioning
confidence: 99%